INTENSIVE METHODS OF TEACHING ENGLISH (Journal of Multidisciplinary Sciences and Innovations, 2025)
Methods, strategies, and techniques for planning and overseeing the language learning process are all part of the English language teaching methodology. For teachers, the English language teaching methodology is crucial because it makes the students' language learning process engaging and successful. The field of English teaching methodology is intricate and multidimensional, requiring a thorough comprehension of pedagogical principles, learner needs, and theories of language acquisition. This article examines intensive methods of teaching English as a foreign or second language, exploring their theoretical underpinnings, pedagogical approaches, and practical applications. It reviews prominent intensive methods, such as Total Physical Response, Suggestopedia, and the immersion approach, analyzing their strengths, weaknesses, and suitability for different learner profiles and contexts. The article also considers the role of learner motivation, teacher training, and assessment in the successful implementation of intensive teaching strategies.